1967
DOI: 10.1017/s0022143000019742
|View full text |Cite
|
Sign up to set email alerts
|

Internal Structure of Sandy Glacier, Southern Victoria Land, Antarctica

Abstract: This narrow, 600 m. long cirque glacier is apparently composed throughout of alternating layers of ice and sand that strike parallel to the edge of the glacier and dip into the glacier at an angle of 82°. The thickness of the sand layers averages 10 cm., and that of the ice layers 20 cm. The sand layers are generally composed of thin parallel laminations but micro-cross-bedding is present locally. The layers have been broken into angular blocks 0.5 to 3.0 m. long, separated by ice columns connecting adjacent i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…An important outcome of differential ablation caused by surface sediment accumulation is the development of hollows, ice cliffs, ponds and streams (Dort, ; Iwata et al ., ) (Figure ). Such morphological and hydrological changes have implications for understanding and subsequently modelling drainage processes on glacier surfaces.…”
Section: Discussionmentioning
confidence: 99%
“…An important outcome of differential ablation caused by surface sediment accumulation is the development of hollows, ice cliffs, ponds and streams (Dort, ; Iwata et al ., ) (Figure ). Such morphological and hydrological changes have implications for understanding and subsequently modelling drainage processes on glacier surfaces.…”
Section: Discussionmentioning
confidence: 99%
“…Distinctly different behavior can be inferred from observations in cold englacial debris bands with more densely packed debris. Among the most striking examples of this are the observations of Wakefield Dort, Jr. and colleagues at Sandy Glacier, Wright Valley, Antarctica [ Dort , ; Dort et al, ]. During a fortuitous visit in 1965, these authors found extensive exposures of interbedded glacier ice and frozen sand emerging near the glacier terminus.…”
Section: Field Observationsmentioning
confidence: 90%
“…The relatively small size and angular edges of the sandy blocks and the clear ductile distortion of the surrounding ice (visible due to alternating clear and bubbly ice layers) attest to the relatively strong, rigid behavior of the frozen sand. This figure is reproduced from Dort [] with permission from the International Glaciological Society and the photographer, Dr. Wakefiled Dort Jr.…”
Section: Field Observationsmentioning
confidence: 99%
“…The expected rapid response of snowpacks to atmospheric conditions could also make them a good proxy for short-term climate change. However, despite the important role buried snowpacks play in the Antarctic (Dort 1967), there is very little knowledge regarding the stability and durability of such snowpacks in the Dry Valleys.…”
Section: Introductionmentioning
confidence: 99%